Tropidoatractidae fam. nov., a Deep Branching Lineage of Metopida (Armophorea, Ciliophora) Found in Diverse Habitats and Possessing Prokaryotic Symbionts - Rotterová, Johana; Bourland, William; Čepička, Ivan (Protist, 2018)
We report a discovery of a novel family of anaerobic ciliates, Tropidoatractidae fam. nov. Phylogenetic analyses based on the 18S rRNA gene show that the family Tropidoatractidae corresponds to the previously reported clade of environmental sequences closely related to the lineage consisting of orders Metopida and Clevelandellida. The family comprises two genera, Tropidoatractus and Palmarella, and five species, two of which are newly described herein. Tropidoatractidae are cosmopolitan Metopida with sparse somatic and oral ciliature, deep, cup-like buccal cavity, and hyaline cortex with interkinetal ridges. Moreover, all species occur in two morphotypes, slender and stout. They inhabit microoxic or anoxic freshwater, brackish, and marine sediments and possess anaerobic mitochondrion-related organelles and various prokaryotic symbionts. The discovery of Tropidoatractidae provides valuable information about the evolution of Armophorea and gives us insights to the diversity and ecological preferences of anaerobic ciliates in general.
Keywords: Sequence Analysis, DNA; Microscopy, Electron, Scanning; anaerobióza; Anaerobic ciliates; fluorescenční mikroskopie; ekosystém; new species; Microscopy, Fluorescence; 18S rRNA gene.; mikroskopie elektronová rastrovací; DNA, Ribosomal; Anaerobiosis; Cluster Analysis; protozoální DNA; RNA ribozomální 18S; protargol; Microscopy; mikrobiologie vody; fylogeneze; RNA, Ribosomal, 18S; ribozomální DNA; sekvenční analýza DNA; Water Microbiology; phylogeny; DNA, Protozoan; Ciliophora; Ecosystem; Phylogeny; mikroskopie; shluková analýza